Passivity as value orientation of individual in modern society (Journal of Philosophy Culture and Political Science, 2019)
In this article the problem of passivity considered as a basic value orientation of human. By passivity we mean the lack of personal interest to the social and political life. A replacement of the active position in life is passion for the esoteric, sects. One reason for the formation of such a value orientation is rampant consumption in modern societies. In this article analyzes the modern foreign sources. Gives ideas from the speeches of our home and Russian philosophers, also considered a number of ﬁ lms that reﬂ ect the problem of passivity in modern society. This phenomenon is characteristic of the modern post-industrial countries.